The management of eczema in children. Issue 2 (February 2015) - Sharma, Ashish; Loffeld, Annette
Abstract: Atopic eczema (AE) is a chronic, itchy, inflammatory skin condition that affects 10–20% of children in developed countries. It is a relapsing and remitting condition, with episodes of disease exacerbation as frequently as two or three times per month. In severe cases it may become continuous. The term 'atopy' is derived from the Greek word meaning "without place, unusual" and implies a genetic predisposition to develop eczema, asthma and hayfever. Some children with AE develop lifelong disease and others go on to develop asthma and allergic rhinitis, in a sequence referred to as the 'atopic march'. This article details the current therapies available for treating children with AE, with practical advice on management and reference to the most recent guidelines.